Learning Difficulties and Learning Expected by Students in the Biochemistry Course at Department of Science Education UIN Fatmawati Sukarno Bengkulu - Qomariah Hasanah; Edi Ansyah (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Biochemistry is a science that has a broad scope of material regarding the chemical-biological and chemical-physiological processes of living things. Biochemistry material that tends to be abstract with pictures and schematics makes it difficult for students to understand biochemistry. The research purpose is to analyze the students' learning difficulties in studying biochemical material and find solutions. The analysis data were obtained through a short questionnaire using the Google form. The research subjects were 40 students of Department of Science Education at UIN Fatmawati Sukarno Bengkulu who had taken courses related to biochemistry. The data were analyzed using the percentage technique. The results showed that the learning difficulties experienced by students regarding the subject matter of Biochemistry were about biochemical terms, molecular structures, metabolic pathways, and biochemical processes. The students learn biochemistry dominated by group discussion methods and lecturer explanations and assisted by video and image explanations. Learning sources in exploring biochemical material are through the internet (scientific articles, videos, pictures), discussions with lecturers, colleagues, and textbooks. To overcome the problem of student learning difficulties, it is necessary to use simple language, deliver sequential material, develop e-module teaching materials, and link biochemical materials in everyday life.